DEVELOPMENT AND PSYCHOMETRIC PROPERTIES OF INDIGENOUS ADJUSTMENT PROBLEM SCALE IN PAKISTAN IAPS-P (The Research of Medical Science Review, 2024)
This study developed and validated the Adjustment Problems Scale (ADPS) to assess marital adjustment challenges in newlywed couples in Pakistan. The sample included 25 couples (25 females and 25 males) were interviewed for this research, who had been living together for the past two years. A snowball sampling technique was used to collect data and open-ended interviews were conducted to identify scale items, followed by a pilot study with 10 couples to refine the tool. Expert validation ensured its relevance, and principal component analysis resulted in a 37-item scale with high internal consistency (Cronbach’s alpha = .88). Exploratory factor analysis revealed five dimensions: Competence, Depression, Anxiety, Loneliness, and Somatic Symptoms. The results demonstrated that the ADPS is a reliable and psychometrically sound instrument. Demographic analyses revealed significant differences in adjustment problems based on variables such as education, gender, family type, marriage type, marriage duration, residence, and consanguineous marriage. However, no significant differences were observed concerning relationship quality, family income, or age. This scale provides a valuable tool for assessing and addressing adjustment issues in newlywed couples, facilitating targeted interventions and future research in marital adjustment.